2018
DOI: 10.15171/jcs.2018.030
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Pain Indicators in Patients with Traumatic Brain Injury Admitted to an Intensive Care Unit

Abstract: Introduction: A consistent approach to pain assessment for patients admitted to intensive care unit (ICU) is a major difficulty for health practitioners due to some patients’ inability, to express their pain verbally. This study aimed to assess pain behaviors (PBs) in traumatic brain injury (TBI) patients at different levels of consciousness. Methods: This study used a repeated-measure, within-subject design with 35 patients admitted to an ICU. The data were collected through observations of nociceptive and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Our results showed that behavioral responses may be valuable indicators of pain assessment in TBI patients. Likewise, American nursing society and the society of critical care suggest behavioral responses for pain detection in patients who are not able to express their pain since these responses rely on the individual pain tolerance and usually manifest in appearance and body movements such as squeezing teeth, holding the painful part, bending, moaning, crying, and uneasiness (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that behavioral responses may be valuable indicators of pain assessment in TBI patients. Likewise, American nursing society and the society of critical care suggest behavioral responses for pain detection in patients who are not able to express their pain since these responses rely on the individual pain tolerance and usually manifest in appearance and body movements such as squeezing teeth, holding the painful part, bending, moaning, crying, and uneasiness (29).…”
Section: Discussionmentioning
confidence: 99%
“…In phase II, 88% of the participants reported likewise and in phase III, the results were similar although the percentage of participants who indicated so fairly reduced to 64%. In individuals who are unable to self-report pain due to various reasons, pain indicators may present as behaviours that are characteristic of other unmet needs [24]. The pain behaviour presents the way in which someone, in this case the clinician, can see that the other person (patient) is in pain.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters evaluated by these tools are physiologic parameters, verbal response, motor response, or facial mimic, which may be irreversibly impaired by brain damage. A study conducted by Nazari and coworkers showed that most of the behaviors that have been observed during painful stimulation in patients with traumatic brain injury included facial expressions, sudden eyeopening, frowning, lip changes, clear movements of extremities, neck stiffness, and sighing or moaning (22). Using these tools may be helpful, but also misleading in patients with brain edema after hypoxic brain injury, or in patients with intracranial hemorrhage and hypertension.…”
Section: Pain Assessment Tools and Patients With Altered Mental Statusmentioning
confidence: 99%